A Framework for Assessment for Learning: Implications for Feedback Practices within and beyond the Gap. (22nd April 2013) - Tan, Kelvin
Abstract : Three recurring emphases in the literature on formative assessment are (a) the importance of assessment design in prompting and sustaining students' learning, (b) giving students feedback that enables them to improve their work, and (c) clarity of standards to articulate the gap between past and desired performances. Much has been written on how each of these is important in designing and using assessment for learning. But there is considerably less attention (if any) on how these emphases should confluence each other. In this paper, I propose a framework for assessment for learning (AfL) wherein assessment standards (vertical axis), task design (horizontal axis) and feedback practices (incline) form a "triangle of practices" that construct the "space" for enhancing learning. Implications for formative assessment to extend learning beyond its triangulated frame are discussed.